2016
DOI: 10.1002/jeab.226
|View full text |Cite
|
Sign up to set email alerts
|

Effects of signaling on temporal control of behavior in response‐initiated fixed intervals

Abstract: Behavior and events distributed in time can serve as markers that signal delays to future events. The majority of timing research has focused on how behavior changes as the time to some event, usually food availability, decreases. The primary objective of the two experiments presented here was to assess how behavior changes as time passes between two time markers when the first time marker was manipulated but the second, food delivery, was held constant. Pigeons were exposed to fixed-interval, response-initiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…The delay‐discounting task consisted of repeated choices between an SSR and an LLR. The SSR was always a signaled response‐initiated fixed‐interval (RIFI) 5‐s schedule (Fox & Kyonka, 2013, 2015, 2016), resulting in the delivery of one food pellet. The LLR was a signaled RIFI schedule with delays of 5, 10, 15, 20, 30, and 40 s, resulting in the delivery of two food pellets.…”
Section: Methodsmentioning
confidence: 99%
“…The delay‐discounting task consisted of repeated choices between an SSR and an LLR. The SSR was always a signaled response‐initiated fixed‐interval (RIFI) 5‐s schedule (Fox & Kyonka, 2013, 2015, 2016), resulting in the delivery of one food pellet. The LLR was a signaled RIFI schedule with delays of 5, 10, 15, 20, 30, and 40 s, resulting in the delivery of two food pellets.…”
Section: Methodsmentioning
confidence: 99%
“…We used a task modeled after one reported by Green and Estle (2003), which has demonstrated strong test-retest reliability and superior discrimination of delays compared to other similar tasks (Peterson et al, 2015). In the task, the SSR option was always a signaled response-initiated fixedinterval (RIFI) 5-s schedule (Fox & Kyonka, 2016) resulting in the delivery of one food pellet, and the LLR option was a signaled-RIFI schedule with delays of 10, 20, and 30 s resulting in the delivery of two food pellets. For both options, a single response was required to initiate the FI and resulted in the illumination of the corresponding light above the lever and the retraction of the alternative lever.…”
Section: Methodsmentioning
confidence: 99%
“…Preference for generalized tokens was sensitive to their price relative to the available alternatives. Fox and Kyonka (2016) evaluated how changing the location and color of an illuminated response key affected the pigeons' ability to use their own behavior as temporal cues in interval schedules of food reinforcement. They found that signaled responses were more effective time markers than unsignaled responses but less effective time markers than stimulus changes that were not response contingent.…”
Section: T4mentioning
confidence: 99%